Professor Henry Ivanovich Turner (1858–1941) (on the 165th anniversary of his birth) - Al. A. Kurygin; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
Outstanding orthopedic surgeon, scientist, teacher and public figure, founder of Russian orthopedics and creator of the largest orthopedic school, organizer and head of the first department and clinic of orthopedics in Russia at the Military Medical Academy, founder of the first Society of Orthopedic Surgeons (1926), actual state councilor , Honored Scientist of the RSFSR (1927), professor (1895) Henry Ivanovich Turner was born in St. Petersburg on September 29, 1858 in a family of British subjects. In 1881, he graduated from the Imperial Military Medical Academy with a doctor’s diploma with honors. In 1892, he defended his doctoral dissertation “On the anatomy of the cecum and vermiform appendix in relation to the pathology of perityphlitis”. In 1895, H. I. Turner was appointed extraordinary professor, and in 1900, he was elected ordinary professor of the department of desmurgy and mechanurgy of the Military Medical Academy. At his request in 1900, the department was transformed into the first department of orthopedics in Russia with a clinical hospital under the leadership of Henry Ivanovich. He took an active part in educational work among the population on the prevention of diseases and injuries and in practical training in first aid techniques for victims. He made a huge contribution to organizing the provision of orthopedic and social assistance to disabled children. As the director of an orthopedic clinic, he performed free operations on children with congenital and acquired pathologies of the musculoskeletal system. H. I. Turner published more than 179 scientific papers on orthopedics and traumatology and actually laid the foundations of a new medical specialty in Russia. Henry Ivanovich was an honorary member of the Pirogov Surgical Society in St. Petersburg and Leningrad, Moscow and other surgical societies, an honorary member of the American and British Orthopedic Associations, a corresponding member of the American Academy of Surgeons, and a member of the International Society for Aid to Crippled Children. Professor H.I. Turner died on July 20, 1941 and was buried in Leningrad at the Bolsheokhtinsky cemetery. Currently, the department and clinic of military traumatology and orthopedics of the S. M. Kirov Military Medical Academy and the National Medical Research Center for Pediatric Traumatology and Orthopedics in St. Petersburg bear the name of H. I. Turner.